Persuasive Anxiety: Designing and Deploying Material and Formal Explorations of Personal Tracking Devices. (2nd November 2017) - Gross, Shad; Bardzell, Jeffrey; Bardzell, Shaowen; Stallings, Michael
Abstract : Self-tracking refers to the use of computational sensing devices that track data about user behavior to provide self-knowledge. Self-tracking devices are often designed to function transparently, with minimal user awareness of the tracking process. Although effective from an information-processing perspective, this invisibility can also background issues of materiality and user experience. Further, research on self-tracking has shown that devices are often abandoned, can cause user anxiety, and reflect hegemonic social norms. Self-tracking is an emerging technology and skilled cultural practice, but its central issues—the space of design possibility, the nature of user needs/experiences, and sociopolitical implications—remain unclear. We present Persuasive Anxiety, a project informed by research through design, critical design, and design deployment studies. We report on the design and longitudinal deployment of three designs—Candy Camera, Melody Bot, and Fractured View—to spark critical dialogue about self-tracking. The project helped reveal some the relationships between self-tracking and destructive social norms, as well as how they might be mitigated; the emergence of self-tracking as a performative cultural skill; and the possibility of bringing digital content authoring tools/research into a closer dialogue with self-tracking to give self-trackers greater agency over this cultural practice.